Assessing the impact of Rwanda trade integration on inclusive growth - Niyonzima, Emmanuel; Ndamsa , Dickson Thomas (Journal of Economics and Business Letters, 2023)
This paper analysed the impact of trade integration on inclusive growth in Rwanda using time series data from 1992 up to 2022. This study used the Fully Modified Least Squares approach to internalise the problem of endogeneity due to omitted variables and feedback effect. This study revealed evidence of deep connection between the five independent variables (trade integration, Import duties, foreign direct investment, Exchange rate, CPI inflation) and the inclusive growth of the Rwandan economy. Besides, these results indicated that an increase in trade integration is expected to increase inclusive growth in the economy of Rwanda.